Measurement of the B± production asymmetry and the CP asymmetry in B±→J/[psi]K± decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2017)
The B± meson production asymmetry in pp collisions is measured using B+→¯D0π+ decays. The data were recorded by the LHCb experiment during Run 1 of the LHC at center-of-mass energies of √s=7 and 8 TeV. The production asymmetries, integrated over transverse momenta in the range 2<pT<30 GeV/c, and rapidities in the range 2.1<y<4.5 are measured to be Aprod(B+,√s=7 TeV)=(−0.41±0.49±0.10)×10−2, Aprod(B+,√s=8 TeV)=(−0.53±0.31±0.10)×10−2, where the first uncertainties are statistical and the second are systematic. These production asymmetries are used to correct the raw asymmetries of B+→J/ψK+ decays, thus allowing a measurement of the CP asymmetry, ACP(B+→J/ψK+)=(0.09±0.27±0.07)×10−2.
R. Aaij, P. d’Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D.Gerick, E. Gersabeck, X.Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, P. Seyfert, M. Schiller, M. Stahl, S. Stemmle, J. v. Tilburg, U. Uwer, M. Vesterinen, R. Waldi, A. Zhelezov [und weitere]
Im Titel wird "psi" als griechischer Buchstabe dargestellt
Im Titel sind "+" und "-" untereinander geschrieben und beide hochgestellt
Gesehen am 30.10.2018